Assessing land cover changes derived from satellite images as an indicator for sustainable land use in Skiathos and Skopelos Islands in Greece - Hadjimitsis, Diofantos G.; Clayton, C.R.I.; Retalis, Adrianos; Zlatoudis, A. (My University, 2001)
This paper examines the potential for using satellite remote sensing techniques to assess and map land cover changes in the Skiathos and Skopelos Islands of Greece. In both Islands tourism is a driving force in the regional economic development and influences the landscape. Any changes in landscape have considerable effects on sustainable land use development of both islands. Last August a fire occurred in Skiathos during its high season tourism period, burning large areas of pine forest. The occurrence of fires on Skiathos is considered as an example for investigating the possible impact of fires on tourism activities and the possible changes in the land use. Land cover changes have been derived from three Landsat-5 TM satellite images acquired in 1988, 1999 and 2000. Classification and change detection techniques have been performed to map land-cover changes in both islands, and compared to the results from other remote sensing algorithms, such as the NDVI (Normalized Difference Vegetation Indices) and SAVI (Soil-Adjusted Vegetation Indices) algorithms. The information derived from the satellite images may be used for a variety of purposes; as indicators for sustainable land use; as a guide for taking measures against any future fire events for the further protection of the islands’ physical treasures; and finally for the assessment of landscape changes with time, and thus for relating changes to corresponding tourism development
Keywords: Satellite images; Satellite remote sensing techniques; Land changes; Skiathos Island; Skopelos Island